Evaluation of a Polyherbal Formulation for antiurolithitic activity: A Biochemical and Histopathological analysis in ethylene glycol induced rat model (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Urolithiasis (kidney stones) is a prevalent urinary system disorder affecting populations worldwide and has been recognized as a long-standing human ailment, contributing to renal failure while various conventional therapies exist for urolithiasis, they are often associated with undesirable side effects. In India, numerous herbal formulations are utilized for treating urolithiasis, known for their efficacy and safety. Specifically, extracts from Celosia argentea seeds, Cissampelos pareira roots, and Bergenia ligulata rhizomes exhibit anti-urolithitic activity. However, combining these herbs in a particular ratio often yields greater therapeutic effects and reduces toxicity compared to using single extracts. Therefore, this research designed to scientifically evaluate anti-urolithic efficacy of polyherbal formulation against urolithiasis using an ethylene glycol (EG)-induced model in rats. Rats were administered EG (0.75 v/v) with water for 28 days to cause renal stone formation, and simultaneously received a single dose of the herbal formulation orally once daily. On day 28, 24-hour urine and serum samples were collected, along with kidney homogenate, for biochemical analysis and histological examination. Cystone was used as a standard herbal formulation for comparison. The co-administration of the polyherbal formulation resulted in substantial (P < 0.001) decrease in urinary and serum levels of renal stone promoters such as calcium, oxalate, phosphate, uric acid, and urea, as well as a significant increase in magnesium and citrate. Histological analysis demonstrated reduced renal cell damage in the treatment group. These results indicate that the polyherbal formulation possesses anti-urolithic activity and holds promise for the treatment of renal calculi.